Regulation of HIV-1 Genome Fate by 5'UTR Structural Dynamics - Brigham, Benjamin. (Tufts University. Tisch Library., 2020)
Thesis (Ph.D.)--Tufts University, 2020.; Submitted to the Dept. of Cell, Molecular & Developmental Biology.; Advisor: James Munro.; Committee: Andrew Bohm, James Baleja, and Claire Moore.; Keywords: Biophysics, Virology, and Biochemistry.